Cytotoxic effect of methanol extract of Conyza bonariensis on DMBA-induced skin carcinogenesis: An in vivo study (Bangladesh Journal of Pharmacology, 2015)
In the present study, we examined the cytotoxic effect of Conyza bonariensis (methanolic extract). The skin carcinogenesis was induced in two stages, first, applying tumor initiator, 7-12-dimethyl benz(a)antheracene and thereafter applying croton oil, a tumor promotor in Swiss albino mice. The morphological alterations observed and measured during the induction of skin ulceration, included; cumulative number of papilloma, tumor yield and tumor burden. C. bonariensis extract (300 and 600 mg/kg/day) was applied locally on mice skin for 16 weeks. The higher dose (600 mg/kg/day) inhibited the tumor formation up to 40% and showed a significant decline in cumulative number of papilloma of continuous group. The results indicated that extract increased the reduced glutathione, superoxide dismutase  and catalase, and decreased lipid peroxidation compared to carcinogen group. Histopathological changes showed papilomatosis and ulceration in carcinogen control group.  HPLC analysis indicated the presence of  flavonoid i.e. quercetin which may be responsible for the cytotoxic action of C. bonariensis methanol extract.